ANALISIS PENGEMBANGAN MOTORIK KASAR ANAK USIA DINI PADA USIA 5-6 TAHUN MELALUI TARI GAMBYONG DI TK TUNAS MEKAR SURAKARTA - Laksmitasari, Dhinai; Feri Faila Sufa; Oka Irmade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the development of gross motor skills in early childhood aged 5–6 years through Gambyong dance activities at TK Tunas Mekar Surakarta. The research is motivated by the fact that many children still show low gross motor abilities, such as limited balance, coordination, body control, agility, and flexibility during physical activities. Using a qualitative phenomenological approach, the study focuses on understanding children’s experiences while participating in Gambyong dance and how these activities stimulate gross motor development. Data were collected through participant observation, semi‑structured interviews with teachers and school principals, and documentation in the form of photos, videos, and school records. The subjects were five children aged 5–6 years who regularly took part in Gambyong dance sessions twice a week using purposive sampling. The findings show that the implementation of Gambyong dance, carried out through stages of planning, implementation, and evaluation, is able to stimulate improvements in children’s balance, coordination of hand–foot movements, body control, locomotor and non‑locomotor skills, strength, agility, and movement flexibility. Children become more confident, more active in participating in movement activities, and increasingly able to follow rhythmic patterns and movement sequences demonstrated by the instructor. Thus, Gambyong dance functions not only as cultural preservation but also as an effective medium to support gross motor development in early childhood education settings.